2012
DOI: 10.1007/s10948-012-1649-3
|View full text |Cite
|
Sign up to set email alerts
|

Coercivity Control of Variable-Length Iron Chains in Phthalocyanine Thin Films

Abstract: The magnetic characteristics of iron phthalocyanine thin films are studied with a vibrating sample magnetometer, identifying a ferromagnetic transition temperature at 4.5 K. The metal ions at the center of the molecule are self-assembled along chains producing quasi one-dimensional magnetic chains of variable length in the thin films. The average chain length is varied from 20 to 300 nm via substrate temperature during deposition. Below the critical transition temperature, the magnetization curves have the sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Increasing the crystallinity of the films and grain size has already been shown to have a large effect on the magnetic properties . These effects can be further explored with the FePc nanowires.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing the crystallinity of the films and grain size has already been shown to have a large effect on the magnetic properties . These effects can be further explored with the FePc nanowires.…”
Section: Resultsmentioning
confidence: 99%
“…We then investigate FePc nanowires, which represent a particularly interesting system as the chain length can be up to five orders of magnitude larger than for the films, a configuration that significantly improves the electronic transport properties . It has already been shown that the length of the iron chains also strongly influences the magnetic properties, with an increase in coercive field observed for increasing crystal size . Therefore, new behaviors are expected for FePc nanowires with the magnetic anisotropy of the molecular plane competing with the shape anisotropy of the nanowires.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we refer to this polymorphism as α + . FePc TFs have been reported to become ferromagnetically correlated at temperatures below 20 K 14 and exhibit a ferromagnetic transition at 4.5 K, very similar to the transition temperature in powders at 5 K …”
Section: Introductionmentioning
confidence: 71%
“…A fruitful and powerful method to distinguish different types of spin configurations is the first order reversal curves (FORC) method well developed theoretically [17][18][19] and tested experimentally for inorganic ferromagnets [20,21], and metal-organic films [22]. A method similar to the FORC one and applicable to thermal hysteresis was developed for single molecular complexes [23][24][25] and microparticles [26].…”
Section: Introductionmentioning
confidence: 99%